Blast analysis of efficient honeycomb sandwich structures with CFRP/Steel FML skins - Patel, Murlidhar; Patel, Shivdayal; Ahmad, Suhail (International journal of impact engineering, 2023)
•Novel efficient design of honeycomb sandwich structures were developed using a FML skin of carbon/epoxy and steel.•The FML used honeycomb sandwich structure provided an excellent blast resistance in comparison to the metallic honeycomb structure.•The Al foam-filled honeycomb has less core crushing than an empty honeycomb core.•FML as front skin and steel as back skin of honeycomb structure showed the smaller deformation in comparison to the other combinations of FML and steel skin used square honeycomb structure. The explosive blast is a major threat in the form of a terrorist attack to damage defense, aerospace, as well as civilian structures. This hazard of an explosive attack affects the lives of people and property. As a result, the modern era is searching for blast resistance structures to save humans and properties from these serious attacks. However, the current numerical analysis represents an effort in the novel design of blast-proof sandwich structures to meet the current era's demand. A stainless-steel sandwich structure using a square honeycomb core was designed to perform conventional weapons effects program (CONWEP) air-blast analysis on ABAQUS/Explicit. After a mesh sensitivity study and validation of the steel sandwich structure with experimental data published in the literature, the effect on blast characteristics of the aluminum (Al) foam-filled honeycomb and carbon fiber reinforced polymer (CFRP) with steel skins using fiber metal laminate (FML) for the front, back, or both skins of the sandwich structure was investigated. The entire finite element (FE) modeled sandwich structures were subjected to 1 to 10 kg of TNT air-blast loads at stand-off distances (SoD) ranging from 150 mm to 200 mm, and their blast resistance performance was evaluated using skin deflection and energy absorption. The damage initiation and evolution of composite laminates in the FML skins were investigated by the Hashin, Puck, and Singh failure criteria, respectively. These criteria were implemented via the VUMAT code. The obtained results showed that using FML skin for the sandwich structure diminished both the front and back skin deflection while improving specific energy absorption. A positive impact on blast mitigation by sandwich structures was observed with an increase in SoD. The lightweight FML front skin and steel back skin used bare square honeycomb hybrid sandwich structure had the smallest back skin deflection and the highest energy absorption up to 3 kg TNT. For the same combination of skins, the hybrid sandwich with foam-filled square honeycomb core represented a positive impact on the blast proof characteristics for high-intensity blasts ranging from 5 kg to 10 kg TNT. However, the novel designed hybrid sandwiches are recommended as a protective structure for defense, ships, automotive, etc.